Coastal Area Development Through Mangrove Planting and Tree Foster Parents (OTAP) as Climate Change Restoration and Mitigation Efforts Sedari Village, Cibuaya District, Karawang Regency - Putra, M.Andhika; Ismail, Taufik; Insani M, Cita (Riviera Publishing, 2022)
Introduction: The global community is faced with some problems such as the climate crisis. The coastal area is one of the areas that are at risk of abrasion and the impact of the climate crisis. Sedari Village is one of the areas in the coastal area that has the risk of abrasion and climate change. This study aims to analyze coastal area development through mangrove planting and tree foster parents (otap) as climate change restoration and mitigation efforts. Methods: The community empowerment program in Sedari Village consists of several stages, namely institutional. formation, institutional training, and biophysical development through mangrove planting. Result: PT Pertamina Patraniaga Fuel Terminal Cikampek conducts a coastal area development program through mangrove planting and tree foster parents. Community empowerment activities aim to map the activities needed for environmental restoration. The Biodiversity and Community Empowerment Program are carried out through many pre-activity stages, from implementation to monitoring and evaluation. Conclusion: Based on community empowerment activities, it is concluded that coastal area development activities through mangrove planting and OTAP initiation have a high urgency value.